Childhood abuse and adverse experience in adolescents who harm others - Doyle, Rebecca Louise (2014)
This thesis explores the effects of adverse childhood experience, including childhood abuse and neglect, on adolescents. More specifically, it explores these effects in relation to offending behaviour. A literature review considered research investigating differences between sexual and non-sexual offenders. More consistent differences were identified for adolescents who sexually offend against children, as opposed to those who offend against peers / adults, when compared to other groups of offenders. Studies in this area are, however, subject to methodological limitations. Following this, an empirical research project investigates the prevalence and characteristics of adverse childhood experience in a sample of mixed sex adolescents detained in a medium secure specialist psychiatric hospital, alongside psychopathological traits. Male sexual offenders differed from violent offenders on a number of variables, including experiences of sexual abuse and a diagnosis of a Learning Disability (LD). Then, a single case study is highlighted which investigates and demonstrates the influence of adverse childhood experience and cognitive impairment on vulnerabilities and offending behaviour in an adolescent male detained in the aforementioned secure psychiatric hospital. The effectiveness of the intervention, designed to address this individual’s difficulties with emotional recognition and regulation, is demonstrated by changes in psychometric assessments scores and via clinical observation of behaviour. Finally, a critique is presented of the Coping Responses Inventory – Youth Form (CRI-Y) (Moos, 1993). This is a psychometric measure designed to measure styles of coping in adolescents. It is critically evaluated to demonstrate its psychometric properties, and its validity for clinical settings. This thesis emphasises the importance of considering developmental experience in the onset of offending behaviour, and the importance of engineering more comprehensive, systemic, and targeted early intervention programmes for individuals deemed at risk of committing particular offences or becoming delinquent in adolescence.